The Familial Adenomatous Polyposis. A Difficult Problem, Between Prevention and Treatment - Giorgio Maria Paolo Graziano Marco Cavallaro; Antonino Graziano (Journal of Surgery and Surgical Research - Peertechz Publications, 2016)
Introduction: The familial adenomatous polyposis of the colon (FAP) is a rare hereditary disease, transmitted as an autosomal dominant trait due to the mutation of the APC gene. The purpose of the study is to assess, even according to the data of our experience, the possibility of clinical application of the results of the new genetic research, linking the problem to prevention and/or treatment. Some operative remarks conclude the study. Materials and methods: We observed (II clinical surgery Garibaldi Hospital in Catania, III Surgery, and Digestive Surgery Unit of the University of Catania) 16 patients on all. In Group I (FAP+) were observed 12 patients with FAP (5 male and 7 female). In group II (FAP-) 4 cases (male). All patients were part of No. 6 families. The diagnostic test and colonoscopy were diagnostics. 8 patients (and all their relatives), performed the genetic typing. Results: The ileo-anal anastomosis with reservoir (IPAA), was, time to time, the operation chosen especially in cases of degeneration in the rectal tract. The ileo-rectal anastomosis (IRA) has been used mostly in the prevention phase of degeneration. The surgical treatment involved 12 patients (Group I). 7 of the cases treated, were subjected to a procedure proctocolectomy and reconstruction by J-pouch ileo-anal anastomosis or latero-terminal ileo-anal anastomosis, with temporary protective ileostomy. One patient underwent definitive ileostomy after proctocolectomy because of cancer involving the ano-pettinea line. The other 4 were subjected to IRA (3), with ileo-rectal anastomosis to 8-10 cm. A patient has developed a pelvic abscess, which required reoperation the definitive iliac anus. Mortality was absent. In the remaining 4 cases of Group II, the genetic test proposed reveal not mutations of the APC gene, so the presumed late degeneration of the polyp did opt for watchful waiting Discussion: The therapeutic approach in FAP is particularly complex and challenging, because it includes the prophylaxis and treatment of the adenomas, for colorectal cancer and ECD (extra colonic diseases) dangerous according to their severity and location. In practice, the FAP has problems similar to the treatment of recto-ulcerative colitis (UC). The indication to anoproctocolectomia with definitive ileostomy can be offered only to those patients (1 case in our series) in which there is an invasive rectal cancer too close or involving the anal rhyme, with diffuse polyposis of the colon. In other cases (2 in our experience one in the rectum, and one in the recto-sigma junction) of cancerous evolution, and when the rectum is intensely involved from polyps (5 of our patients) is preferable to the lPAA and ileo pouch anal anastomosis in J, . In all cases where it is considered possible (4 cases came under our observation) the endoscopic procedure of the rectum and there is no cancer in situ, you can proceed to a total colectomy with ileo-rectum anastomosis about 6 cm or below to achieve good continence. It is advisable to carry out an T-L ileo-rectal anastomosisor with aJ pouch in cases where it is deemed necessary to remove of the proximal rectum with more intensely polyposis. A number of evacuations acceptable (up to 3-5 per day) are the functional results of these predictable surgical options. Dehiscence with sepsis of the small pelvis may complicate the postoperative evolution of IPAA, which can be controlled with a protective ileostomy. He IRA involves especially the risk of degeneration of the residual or recurrent rectal polyps, while the IPAA generally results in imperfect functional results, risk of dehiscence and septic complications Conclusion: The FAP is a rare but potentially lethal disease (responsible for about 1% of all colic cancers, HPCC) for the patient, in which a genetic mutation is transmitted in 50% of the descendants. The introduction into clinical practice of test for molecular diagnosis is the innovation technology, which allows a more accurate assessment of the disease and the best indications of the time and type of treatment and surveillance program. , the prospects of Genetics for further more direct approaches, present choices ethically more complex of prevention and treatment.